Effects of Solution, Soil and Sand Cultures on Nodulation and Growth of Phasey Bean - Wan Othman, Wan Mohamad; Asher, C. J.; Humpherys, L. R (1986)
Plants of phasey bean (Macroptilium lathyroides cv. Murray) were grown in nitrogen-free nutrient solution, sod, or sand culture in a naturally-Nt glasshouse. Nodulation, dry matter accumulation in plant parts, and seed yields were assessed. Partitioning of symbiotic nitrogen into various plant parts during vegetative and reproductive growth stages was also determined. In all culture media, nodule number and size increased with plant age but the rate of increase was generally greater in solution than in the other cultures. In sand culture, the dry weight per nodule and per plant, and plant growth were significantly suppressed. Although tap root elongation was consistently better in solution than soil or sand culture, leaf development and dry matter accumulation in roots and stems were enhanced by solution culture only during flowering and fruiting stage. Seed yields were significantly increased by solution culture, an effect apparently associated with increased symbiotic nitrogen fixation. During vegetative growth, nitrogen accumulated largely in the leaves and stems but pods were major sinks of nitrogen during the reproductive growth stage. The benefits and applications of solution culture in the study of nodule development and collection of root samples for acetylene reduction assays are discussed.